Planning of reconstruction in conflict-affected areas - Al-Bareed, Mohammed (Univerzita Pardubice, 2018)
The aim of this thesis was to evaluate the available data sources and to design the data set that would help to redevelopment and recover the regions and countries affected by a forced conflict, such as Yemen, to help development after the war stops to know where to start the redevelopment of the country and to have a clear idea where needs more attention and what are the priorities when it come to the reconstruction of key sectors of the economy of the country. Based on these findings and the information that are demonstrated in tables 2 and 3, we can conclude that the priority to relief and recover, reconstruct and rebuild is in the health sector and then clean water sources, and especially in the governorate of Sa’ada which had severe damages.
Keywords: regions; regional development; disaster; reconstruction